PENGARUH SOSIOLOGIS TERJADINYA INTERFERENSI BAHASA DAERAH TERHADAP BAHASA INDONESIA DI DALAM PERGAULAN ANGGOTA PRAMUKA IKIP SILIWANGI - Yeremia Junior (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Bahasa Indonesia as the lingua franca for the Indonesian people is often interfered by vernacular languages. One of the factors which affect the languages itself is language diversity. Most of the people do not make Bahasa Indonesia as mother tongue, though it is a lingua franca in Indonesia. The respondents in this study obtained the vernacular languages as a mother tongue. The Scouts member of IKIP Siliwangi came from different regions, which affecting the vernacular language interference into Bahasa Indonesia. This sociological factor affects them in social interactions, which in turn produce language interference both in vocabularies, dialects, accents, to sentence structure in spoken language both intentionally and unintentionally.